Visiting Picasso : poems - Barnes, Jim, 1933- (Urbana : University of Illinois Press, 2007)
Annotation Jim Barnes's familiarity with the European poetic traditions has been deepened through long periods spent in France, Germany, and Italy, and through his translations of European poetry. In Visiting Picasso he repays Europe for its gifts to him in a series of poems that evoke the lush poetic history that ties European culture together, sometimes darkly. A heightened sense of place and purpose infuses the poems of Visiting Picasso with meaning drawn from actual landscapes, events, and observations.
The First Feria of the Third Millennium, Arles Easter MondayIn Aix-en-Provence -- The Poet's Paradise -- Agamemnon -- The Snow Bird -- Twister -- Ikaros 1940 -- Owl -- Rondeau for a Shovelbill Catfish, at the Buffalo Hole, Fourche Maline River, a la Research du Temps Perdu, January 2003 -- Magpie -- West of Cassis -- Taos as Purgatory -- Epithalamion: Villanelle for September 7, 2002 -- In Memory of Dora Maar -- Elegy for the Old Man beside the Road to Nans les Pins -- Villa Serbelloni Revisited, February 2003
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
eBooks on EBSCOhost
Keywords: American poetry -- 20th century; Poésie américaine -- 20e siècle.; POETRY -- American -- General; FICTION -- General; American poetry; 1900-1999; Electronic book